THE EFFECT OF WORK DISCIPLINE, MOTIVATION, AND COMPENSATION ON TEACHER PERFORMANCE SMK YUPPENTEK 1 TANGERANG - Fauzi, Ahmad; Herminingsih, Anik (Dinasti International Journal of Management Science, 2021)
The research aims to analyze the effect of work Discipline, motivation, and compensation on teacher performance. The data analysis is quantitative with the purpose of answering the predetermined research hypotheses. The sampling technique that used in this research is nonprobability technique, with the research subjects totaling 45 permanent teachers who work in the organization of SMK Yuppentek 1 Tangerang. The results obtained, show that: (1) Work discipline partially has a positive and significant effect on the teacher performance, (2) Motivation partially has a positive and significant effect on the teacher performance, (3) Compensation has no significant effect on the performance of teachers at SMK Yuppentek 1 Tangerang.